Beyond Revascularization: Impact of Exercise-Based Cardiac Rehabilitation on Functional Capacity in ACS Complicated by Heart Failure – A Systematic Review and Meta-Analysis - Leoni; Ni Putu Ika Regina Maharani; Stefanus Leonardo Handoko; Ragil Nur Rosyadi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Acute coronary syndrome (ACS) complicated by heart failure (HF) represents a distinct, high-risk phenotype. Even after successful revascularization via percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG), these patients remain vulnerable to maladaptive ventricular remodeling and functional decline. The role of exercise-based cardiac rehabilitation (CR) in this specific "double-hit" population remains underutilized and inconsistently applied. This study aimed to evaluate the effectiveness of exercise-based CR on functional capacity, left ventricular ejection fraction (LVEF), and major adverse cardiac and cerebrovascular events (MACCE) in patients with ACS complicated by HF following revascularization. Methods: We conducted a systematic review and meta-analysis of randomized controlled trials and high-quality cohort studies published between 2019 and 2025. Seven pivotal studies involving 23,663 participants were analyzed. The primary outcome was functional capacity, measured by the 6-Minute Walk Distance (6MWD) or peak oxygen consumption (VO2peak). Secondary outcomes included LVEF and MACCE. Data were pooled using random-effects models. Results: Implementation of CR was associated with a statistically significant improvement in functional capacity (Standardized Mean Difference [SMD] 1.66; 95% Confidence Interval [CI] 0.11–3.22; p=0.04). Cardiac function analysis revealed a clinically meaningful increase in LVEF (Mean Difference +2.58%; 95% CI -0.29 to 5.46; p=0.08) in the CR group. Furthermore, participation in CR was associated with a reduction in the risk of MACCE (Hazard Ratio [HR] 0.80; 95% CI 0.62–1.03; p=0.09), with long-term survival benefits observed in large cohort subsets. Conclusion: Exercise-based CR provides critical physiological benefits beyond those achieved by revascularization alone. The significant restoration of functional capacity and favorable effects on cardiac remodeling underscore CR as an essential, non-negotiable pillar of care for patients with ACS complicated by heart failure.